2015
DOI: 10.5455/2320-6012.ijrms20150109
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Oral Methotrexate and Acitretin in the Treatment of Palmoplantar Psoriasis

Abstract: Background: Psoriasis is chronic inflammatory skin condition. Palmoplantar psoriasis is a type where lesions are present on the palms and soles. This type affects patient's quality of life and is difficult to treat. Topical modes of treatment are not so effective and produce inadequate response. Systemic drugs are necessary in the treatment of moderate to severe disease. The objective was to compare the efficacy of oral methotrexate and acitretin in treatment of moderate to severe palmoplantar psoriasis and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We found that mean MASI score at baseline, 1 month, 2 months and 3 months was 58.2, 38.4, 23.2 and 14.6 and 60.4, 40.2, 30.5 and 20.4 in group I and II respectively. Giovanni et al [10] . 17 reported the efficacy of oral acitretin in 42 patients with hyperkeratotic palmoplantar dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…We found that mean MASI score at baseline, 1 month, 2 months and 3 months was 58.2, 38.4, 23.2 and 14.6 and 60.4, 40.2, 30.5 and 20.4 in group I and II respectively. Giovanni et al [10] . 17 reported the efficacy of oral acitretin in 42 patients with hyperkeratotic palmoplantar dermatitis.…”
Section: Discussionmentioning
confidence: 99%